Detection of voltage disturbances in power quality using wavelet transforms - Ramlee, Nor Asrina (2012)
Power quality has cause a great concern to electric utilities with the growing use of sensitive and susceptive electronic and computing equipment. The best analysis on power quality is vital to provide better service to customers. This paper presents the detection of voltage sag and voltage swell event using four types of mother wavelet namely Haar, Dmey, Daubechies and Symlet to identify the most accurate mother. The method is developed by applying time domain signal analysis using Discrete Wavelet Transform (DWT) as a detection tool in MATLAB. The actual interrupted signals were obtained from 22kv transmission line in Skudai, Johor Bahru. They will be decomposed through the wavelet mothers. The best mother is the one that capable to detect the time location of the event accurately